Analisis keterampilan sosial dalam dimensi hubungan teman sebaya pada buku ajar IPAS SD Kelas IV - Nando Ryan Saputra; Karsono Karsono; Fadhil Purnama Adi (Didaktika Dwija Indria, 2023)
The aim of the study was to describe the social skills in peer relations contained in the textbooks of Natural and Social Sciences (IPAS) for fourth grade students in the Merdeka Curriculum. This research is included in the type of content analysis research. This research is a descriptive qualitative research, this is because this research describes the reality of social skills in peer relations. Data collection techniques used were document inspection and interviews. Data validity testing techniques use techniques to increase persistence and use content validity of logical validity types. This study uses the interactive data analysis technique of the Miles and Huberman model. The results of the study concluded that social skills in peer relations which consisted of indicators of positive interaction with peers and having empathy with peers were included in the learning activities in the Natural and Social Sciences textbooks for fourth grade students of Merdeka Curriculum Elementary School. However, the level of domination of the development of each indicator of social skills in peer relations varies. Overall, the development of social skills in peer relations in the Natural and Social Sciences Textbook for Grade IV students at Merdeka Curriculum Elementary School has an unequal and uneven distribution pattern.